Ghost companies in Mexico - Isabel García Requenes, J.; Salcedo Triana, Oralia; Ruiz Romo, Daniel; del Pilar Delijorge González , Georgina; María Muñoz Briones , Rosa; Enrique Paredes Berumen, Luis; Aída Rivera Cornejo, Rosa; Enrique Villela Varela , Manuel; Ibarra, Juan Oliver Flores; Rendón, Elisa Dinorah Galaviz (Seven Editora, 2023)
Companies that carry out simulated operations have become a serious problem facing the tax administration in Mexico. These types of companies are known as “ghost” or billing companies. Most of the time, these companies do not have employees or domicile, but they have the papers in order before the corresponding instances, such as registration with the Treasury, before the Ministry of Economy, with constitutive acts, etc., and most importantly: they have stamps to issue invoices for providing services or producing goods that they are unable to provide. They are companies that do not physically exist and are generally used to commit alleged crimes such as tax evasion, money laundering, or the diversion of public resources. The "ghost" companies by themselves do not evade taxes, launder money, nor disappear public resources, but require a whole structure of corrupt officials who design the scheme to simulate contracts to divert the money, as well as multiple operators, such as financial advisors, lawyers, notaries, accounting firms and front names who execute it in the purest style of organized crime, in addition to the collusion of authorities that DOI: https://doi.org/10.56238/devopinterscie-171